Androgen receptor (AR) in cardiovascular diseases. Issue 1 (April 2016) - Huang, Chiung-Kuei; Lee, Soo Ok; Chang, Eugene; Pang, Haiyan; Chang, Chawnshang
Abstract : Cardiovascular diseases (CVDs) are still the highest leading cause of death worldwide. Several risk factors have been linked to CVDs, including smoking, diabetes, hyperlipidemia, and gender among others. Sex hormones, especially the androgen and its receptor, androgen receptor (AR), have been linked to many diseases with a clear gender difference. Here, we summarize the effects of androgen/AR on CVDs, including hypertension, stroke, atherosclerosis, abdominal aortic aneurysm (AAA), myocardial hypertrophy, and heart failure, as well as the metabolic syndrome/diabetes and their impacts on CVDs. Androgen/AR signaling exacerbates hypertension, and anti-androgens may suppress hypertension. Androgen/AR signaling plays dual roles in strokes, depending on different kinds of factors; however, generally males have a higher incidence of strokes than females. Androgen and AR differentially modulate atherosclerosis. Androgen deficiency causes elevated lipid accumulation to enhance atherosclerosis; however, targeting AR in selective cells without altering serum androgen levels would suppress atherosclerosis progression. Androgen/AR signaling is crucial in AAA development and progression, and targeting androgen/AR profoundly restricts AAA progression. Men have increased cardiac hypertrophy compared with age-matched women that may be due to androgens. Finally, androgen/AR plays important roles in contributing to obesity and insulin/leptin resistance to increase the metabolic syndrome.